2013
DOI: 10.1186/1752-1947-7-204
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of bladder metastasis 10 years after surgical removal of a primary gastric cancer: a case report and review of the literature

Abstract: IntroductionSecondary bladder neoplasms are uncommon and they represent only 2% of all malignant bladder tumors.Case presentationThe authors present a case of a 59-year-old Caucasian man with a primary gastric adenocarcinoma that had been surgically removed 10 years before he developed bladder metastasis. He presented with low abdominal pain after 10 years without any symptoms. Cystoscopy and an abdominal computed tomography scan showed a bladder tumor. A transurethral resection of the bladder tumor was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…In a previous study, it was reported that secondary bladder neoplasm represents 2% of the total malignant bladder neoplasm. 16 The percentage of secondary tumours in this current study was much higher than the previous study. The most common histopathology type of secondary bladder cancers reported was adenocarcinoma (36.1%).…”
Section: Discussioncontrasting
confidence: 71%
“…In a previous study, it was reported that secondary bladder neoplasm represents 2% of the total malignant bladder neoplasm. 16 The percentage of secondary tumours in this current study was much higher than the previous study. The most common histopathology type of secondary bladder cancers reported was adenocarcinoma (36.1%).…”
Section: Discussioncontrasting
confidence: 71%
“…In the remainder of the cases, bladder metastasis was observed after a median period of 24 months following the diagnosis of gastric cancer. In one of these cases, recurrence was observed in the bladder 10 years later [8]. Signet-ring cell carcinoma histology was observed in 12 of the cases.The treatment methods administered to these cases included systemic chemotherapy, transurethral resection(TUR) and partial cystectomy [9].…”
Section: Discussionmentioning
confidence: 90%
“…Bladder metastases may not only result from direct expansion of the primary tumor, but also result from the implantation of lymphogenic, hematogenous or peritoneal spread from a distant primary neoplasm. 4 Most of the information about bladder metastatic tumors was obtained from autopsy series. Bates et al reported on 282 patients series containing bladder secondary tumors, organs that metastasize directly to the bladder; are colon (21%), prostate (19%), rectum (12%) and cervix (11%).…”
Section: Discussionmentioning
confidence: 99%
“…Torenbeek et al reported, at least focally, of CK7 in 82% positive of cases and CK20 in 73% positive, whereas a CK20-positive and CK7-negative profile was detected in only 29% of the cases of primary adenocarcinomas of the bladder. 4 In gastric cancer, CK7 is usually positive and CK20 is negative. Mucicarmine is positive at a high rate in mucin producing tumors and particularly in gastrointestinal malignancies.…”
Section: Discussionmentioning
confidence: 99%